Peningkatan Efisiensi dan Penjualan Toko Fashion Outlet Rantauprapat di Jalan Sisingamangaraja Melalui Implementasi E-Commerce PrestaShop - Nasution, Intan Baiduri; Harahap, Syaiful Zuhri; Juledi, Angga Putra (Universitas Labuhanbatu, 2024)
The purpose of this study is to assess the impact of implementing the PrestaShop e-commerce platform on the efficiency and sales of Fashion Outlet Rantauprapat on Sisingamangaraja. Using a case study approach using quantitative and qualitative data, this study analyzes purchase data before to and after PrestaShop implementation, as well as conducts research with store owners. The results of the study show that PrestaShop significantly improves operational efficiency, reduces market volatility, and increases sales. However, challenges such as a lack of technical knowledge and skills must be addressed. This study found that PrestaShop has a large potential to become an effective tool for Fashion Outlet Rantauprapat in terms of increasing sales in the digital era.